2020
DOI: 10.1186/s12885-020-07583-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with breast cancer awareness and breast self-examination in Fiji and Kashmir India – a cross-sectional study

Abstract: Background In low-income countries breast cancer awareness (BCA) is essential to reduce the proportion of advanced stage presentations of breast cancer. There is a lack of studies using multivariable techniques to explore factors related to BCA in low-income countries. The objective of this study was to identify to what extent women in Fiji and Kashmir, India have BCA and practice breast self-examination (BSE) as well as factors associated with BCA and BSE. Methods A survey of women aged ≥18 years was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Some earlier studies provided lower levels of knowledge about early warning signs than our research. 11 , 36 , 37 , 38 , 39 That could be due to the education level 48 and the availability of sources of breast cancer information for the study participants. Our research discovered adequate knowledge about screening approaches of breast cancer among medical students and insufficient knowledge among university students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier studies provided lower levels of knowledge about early warning signs than our research. 11 , 36 , 37 , 38 , 39 That could be due to the education level 48 and the availability of sources of breast cancer information for the study participants. Our research discovered adequate knowledge about screening approaches of breast cancer among medical students and insufficient knowledge among university students.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies provided lower levels of knowledge about early warning signs than our research. 11,[36][37][38][39] That could be due to the education level 48 and the availability of sources of breast cancer information for the study participants. the other hand, practicing BSE was least commonly done by university students because of insufficient knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…In a study from Kashmir, India, authors found breast cancer awareness and breast self-examination in 7.35% women. They also concluded that breast cancer awareness was linked to the general education of the women (Malik et al, 2020). As majority of our patients did not have any formal education/ training or exposure about how to practice breast selfexamination, the practice itself might have been rendered ineffective.…”
Section: Discussionmentioning
confidence: 84%
“…İnformation points in two studies conducted on the same scale in Turkey were detected to be moderate. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] In other studies in which women's breast cancer knowledge levels were evaluated with different scales, it was stated that their knowledge level was moderate. 34-82-83-84-85-86-87 In two studies conducted on young women in Ethiopia, the breast cancer knowledge level of women was found as low.…”
Section: Discussionmentioning
confidence: 99%